Bir işletme probleminin parametrik programlama tekniği ile çözümü - Koçak, Habib (Marmara Üniversitesi Sosyal Bilimler Enstitüsü, 1998)
Operations Research techniques as a decision unit seek mathernatical Solutions for business problems. Firm has an a imfunction described with mathernatical symbols. Parametric Programming, examines the aim function över time İn this study optimum production planning model has examined with Parametric Programming technique.